Eigenvalue Distribution of a Large Weighted Bipartite Random Graph - Vengerovsky, V. (Журнал математической физики, анализа, геометрии, 2014)
We study an eigenvalue distribution of the adjacency matrix A^(N,p,a) of the weighted random bipartite graph Г = ГN,p. We assume that the graph has N vertices, the ratio of parts is α(1-α), and the average number of the edges attached to one vertex is ap or (1-a)p. To every edge of the graph eij, we assign the weight given by a random variable aij with all moments finite. We consider the moments of the normalized eigenvalue counting measure sN,p,a of A^(N,p,a). The weak convergence in probability of the normalized eigenvalue counting measures is proved. Исследуется распределение собственных значений матрицы смежности A^(N,p,a) взвешенного случайного двудольного графа Г = ГN,p. Предполагается, что этот граф имеет N вершин, соотношение размера его частей равно α(1-α) и средняя степень вершины равна ap и (1-a)p. К каждому ребру графа eij приписывается в качестве веса случайная величина aij, у которой все моменты конечны. Рассмотрены моменты нормированной считающей меры sN,p,a матрицы A^(N,p,a). Доказана слабая сходимость по вероятности нормированных считающих мер.